2014
DOI: 10.2337/dc13-2176
|View full text |Cite|
|
Sign up to set email alerts
|

Burden of Diabetic Foot Ulcers for Medicare and Private Insurers

Abstract: OBJECTIVE To estimate the annual, per-patient incremental burden of diabetic foot ulcers (DFUs). RESEARCH DESIGN AND METHODS DFU patients and non-DFU patients with diabetes (controls) were selected using two deidentified databases: ages 65+ years from a 5% random sample of Medicare beneficiaries (Standard Analytical Files, January 2007–December 2010) and ages 18–64 years from a privately insured population (OptumInsight, Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
305
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 445 publications
(324 citation statements)
references
References 15 publications
2
305
0
1
Order By: Relevance
“…Medication on the other hand only represented 10% of the total costs. Also in a Medicare analysis done in the United States between 2007 and 2010, hospitalization was found to contribute 62.5% of the total costs of illness while prescription drug contributed only 5.9% [30]. Patients in our study tend to rely on traditional medication and orthodox drugs,for treatment rather than surgical care because of lack of affordability of surgical management.…”
Section: Discussionmentioning
confidence: 68%
“…Medication on the other hand only represented 10% of the total costs. Also in a Medicare analysis done in the United States between 2007 and 2010, hospitalization was found to contribute 62.5% of the total costs of illness while prescription drug contributed only 5.9% [30]. Patients in our study tend to rely on traditional medication and orthodox drugs,for treatment rather than surgical care because of lack of affordability of surgical management.…”
Section: Discussionmentioning
confidence: 68%
“…The incidence in Europe is around 2% per year [8]. Costs of care are double those seen in individuals without ulceration [9], with the total cost associated with treatment being as high as €10 billion per year in Europe [8]. The incidence of foot ulcers is 2.2% per annum in the UK, and an average of 6000 people with diabetes each year undergo amputation [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…For example, prior studies have identified DFU duration as an independent risk factor for the development of a foot infection, and that, the risk of hospitalization was 55.7-times greater and the risk of amputation was 154.5-times greater than those who did not develop foot infections 6 . Approximately 5% of diabetes patients with foot ulceration require a lower-limb amputation within the year following a DFU diagnosis compared to almost no amputations among those without DFUs 7 . Further, foot ulceration is one of the major sources of hospitalizations among patients with diabetes and has been estimated to precede more than four out of every five lower-limb amputations in these patients 4,8 .…”
Section: Introductionmentioning
confidence: 99%